Ricci flow : techniques and applications - Chow, Bennett; Chu, Sun-Chin.; Glickenstein, David; Guenther, Christine; Isenberg, James; Ivey, Tom.; Knopf, Dan .; Lu, Peng.; Luo, Feng.; Ni, Lei. (Providence : American Mathematical Society, 2015)
Gives a rigorous introduction to some of Perelman's work and explains some technical aspects of Ricci flow useful for singularity analysis. The authors have also attempted to give the appropriate references so that the reader may further pursue the statements and proofs of the various results.
pt. IV. Long-time solutions and related topics.
Includes bibliographical references and indexes.
Keywords: Global differential geometry; Ricci flow; Riemannian manifolds